Migration Patterns and Economic Interconnections in the Indian Ocean during the Nineteenth Century - Beatrice Nicolini (Cadernos de Estudos Africanos)
The Indian Ocean acted as a central hub, facilitating relationships between the South-Central Asian littorals, the main coasts of Oman, and the Swahili coasts of East Africa from Mogadishu to Kilwa. The focus of this paper is to reevaluate the migration patterns that shaped East African-Swahili societies during the nineteenth century. However, the available literature on this topic has been limited. Specifically, the Baloch in East Africa during the 1800s have often been viewed as a monolithic presence, associated only with defense military squadrons. Nevertheless, it is crucial to recognize the roles played by Asian communities in East Africa, which challenges the conventional belief that Asian groups only arrived in East Africa as military squads between the eighteenth and nineteenth centuries.